Personality Traits in the Arabic Novel - Naguib Mahfouz and Other Writers – A Model - berbache, meriem; henni, lakhdar (El Omda in Linguistics and Discourse Analysis, 2025)
The Arabic novel is a widespread literary art that reflects human life ‚ including both happiness and misery. Authors use characters to explore social ‚political and religiouse issues‚ portraying their internal conflicts and struggles. These novels gained popularity by addressing social issues like poverty‚ injustice‚ and extremism‚ and by giving consideration to the women situation. The development of the Arabic novel has been influenced by social changes‚ such as those during colonization and postindependence periods‚ with chracters often representing the voce of bpeople seeking freedom.